Evaluación de la viabilidad de aplicación de la tecnología radio corto para la perforación de un pozo en el Campo Rubiales (2018)
This project seeks to evaluate the technical-financial advantages of a short radius directional profile with respect to a directional profile with a negative section currently carried out in Rubiales Field by means of a drilling simulator, in which the design of both wells is presented, then the costs of each project for its final comparison. In order to comply with the development of the work, two processes are carried out, the first is a theoretical one, in which the description of the generalities of the Rubiales Field and its geographical location will be made, a geological framework where the stratigraphic and structural description of the Llanos Orientales’ Basin, where is the area of interest where the well to study is implemented, a theoretical framework that offers the reader the necessary information on each type of directional drilling to achieve a horizontal well along with the tools used and their respective costs.